The Role of Organizational Culture in Improving Lecturer Innovative Work Behavior Sea Transportation Human Resource Development Center - Yustina Sapan; Tri Joko Raharjo; Heri Yanto; Muh. Khafid (International Conference on Science, Education, and Technology, 2021)
The current study is carried out to develop a model of innovative work behavior for lecturers based on organizational culture during the Covid-19 pandemic. This is the background of this research, especially for Lecturer Sea Transportation Human Resource Development Center. This study uses the Multivariate Structural Equation Model (SEM) technique. The sample of this research is the Lecturer Sea Transportation Human Resource Development Center as many as 145 lecturers. The results of this study indicate that the innovative work behavior of lecturers is influenced by 55.7% by the organizational culture where the People orientation dimension dominates.